Determinants of Maternal Health Care Choices among Women in Lunga Lunga Sub County in Kwale County-Kenya - Otieno, Geoffrey Andrew; Owenga, Jane Adhiambo; Onguru, Daniel (World Journal of Innovative Research (WJIR), 2020)
Maternal and neonatal morbidity and mortality are major public health concerns in most developing countries and in under resourced settings. Provision of safe motherhood is of utmost importance in the reduction of maternal mortality. Increasing the proportion of babies that are delivered in health facilities is an important factor in reducing the health risks to both the mother and the baby. This study explored maternal healthcare choices of expectant mothers in Lunga Lunga Sub County, Kwale County. The objectives of the study were; the identification and description of maternal healthcare providers in the area; the examination of the determinants for maternal healthcare choices; and the exploration of the perceptions and attitudes of the local community towards both formal and informal maternal healthcare providers. This was a community based cross-sectional descriptive study, the study employed community survey for which mothers with children below eight months were purposively sampled. Key informant interviews involving twelve maternal healthcare providers, from popular, professional and folk sectors were also purposively sampled to shed light on services they provide to expectant mothers. The study also used focused group discussion of discussants who were sampled by region in the area. Information on maternal health care providers in the area, the kind of maternal healthcare services they provided, social support system and the perception of the community towards maternal healthcare providers was collected guided by the Disease Explanatory Model (DEM) proposed by Kleinman (1980). All analysis was done in SPSS version 21.0 for windows. P-value less than 0.05 was considered statistically significant. Results were considered significant at 95% confidence level. Results of the study indicates that, among the 333 mothers who participated in the study, 293(88%) were married and 219(65.8%) were of Islamic religion. Most of the mothers, 266(85.2%) had not completed Primary level of education. Of all the deliveries, 212(64%) were under skilled attendants at the health facilities. Mothers from Shimoni were less likely to deliver at the hospital as compared to those from Vanga, Mwena, Malamba and Mzizima. Controlling for distance from the facility, Mothers education level, Sub location of residence, presence of a health facility in the locality and mothers preference to a particular Maternal health service provider were significant predictors of choice of place of delivery among the study participants (p<0.05). In conclusion the study revealed that utilization of skilled delivery attendance services was still low than expected with a high number of deliveries being attended by unqualified lay persons at home. There was need to strengthen the education infrastructures, implement cost effective and sustainable measures to improve the quality of maternal health services with an aim of promoting safe delivery and hence reducing maternal mortality.
Keywords: Neonatal morbidity; Maternal health